Analisis praanggapan dalam Iklan Produk Kecantikan di Youtube - Erma Zevira; Armia Armia; Subhayni Subhayni; Ramli Ramli (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
Based on the background of the problem, the problem formulation in this study is what is the presupposition in the advertisement of beauty products on Youtube? and what are the types of presuppositions in beauty product advertisements on Youtube. This study aims to describe presuppositions in beauty product advertisements on Youtube and to describe the types of presuppositions in beauty product advertisements on Youtube?. In this study, the authors choose 15 data sources for advertising beauty products